Serum neurofilament light chain level as a predictor of cognitive stage transition - Eun-Hye Lee; Hyuk Sung Kwon; Seong-Ho Koh; Seong Hye Choi; Jeong-Hwa Jin; Jee Hyang Jeong; Jae-Won Jang; Kyung Won Park; Eun-Joo Kim; Hee Jin Kim; Jin Yong Hong; Soo Jin Yoon; et al. (Alzheimer’s Research & Therapy, 2022)
Abstract Background Neurofilament light chain (NFL) level has been suggested as a blood-based biomarker for neurodegeneration in dementia. However, the association between baseline NFL levels and cognitive stage transition or cortical thickness is unclear. This study aimed to investigate whether baseline NFL levels are associated with cognitive stage transition or cortical thickness in mild cognitive impairment (MCI) and cognitively unimpaired (CU) participants. Methods This study analyzed data on participants from the independent validation cohort of the Korea Brain Aging Study for the Early Diagnosis and Prediction of Alzheimer’s disease (KBASE-V) study. Among the participants of KBASE-V study, 53 MCI and 146 CU participants who were followed up for ≥ 2 years and had data on the serum NFL levels were eligible for inclusion in this study. Participants were classified into three groups according to baseline serum NFL levels of low, middle, or high. Results The Kaplan–Meier analysis showed association between the serum NFL tertiles and risk of cognitive stage transition in MCI (P = 0.002) and CU (P = 0.028) participants, analyzed separately. The same is true upon analysis of MCI and CU participants together (P < 0.001). In MCI participants, the highest serum NFL tertile and amyloid-beta positivity were independent predictors for cognitive stage transition after adjusting for covariates. For CU participants, only amyloid-beta positivity was identified to be an independent predictor. Conclusion The study shows that higher serum NFL tertile levels correlate with increased risk of cognitive stage transition in both MCI and CU participants. Serum NFL levels were negatively correlated with the mean cortical thickness of the whole-brain and specific brain regions.